Unlocking Success: Key Factors for International Mobility Program in Implementing the Merdeka Belajar-Kampus Merdeka Curriculum - Rohmatun Lukluk Isnaini; Wiji Hidayati; Zainal Arifin (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2024)
This article is based on research conducted at nationally accredited State Islamic Higher Education Institutions (PTKIN) in Indonesia, which have already begun implementing the Merdeka Belajar-Kampus Merdeka (MBKM) curriculum. The informants serving as data sources consist of 15 students participating in the International Mobility Program (IMP). A qualitative case study gathered data from interviews, observations, and documentation. The research emphasizes that the determinants of IMP success in supporting the implementation of the MBKM curriculum consist of four aspects: 1) through the ability to adapt well to a new environment, students gain learning experiences outside the campus by adjusting and respecting cultural differences in the destination country; 2) through international language proficiency, students are increasingly trained to conduct high-quality research and communicate effectively creatively; 3) through their interest in challenges and adventures in foreign campuses, students confidently present in international forums; 4) through the transformation of a global perspective, students are motivated to pursue further studies abroad and intend to participate in international programs in the following years. Understanding and emphasizing these factors is crucial for optimizing the benefits derived from international mobility initiatives within the unique context of religious higher education institutions.